“PENGARUH KESADARAN PERPAJAKAN DAN SANKSI DENDA TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA SEMARANG” - INGGRIT MEILANA HALIM, 14.05.52.0287; Sri Mindarti, Ceacilia (Students' Journal of Accounting and Banking, 2019)
One source of regional revenue from the tax sector is the Land and Building Tax. The United Nations is a tax imposed on the earth and buildings. The earth and buildings provide better socio-economic advantages and / or positions for people or entities that have a right to them or benefit from them, and therefore it is natural for them to be obliged to provide a portion of the benefits or pleasures obtained through taxes. One of the factors that influence the success of taxation, especially land and building tax, is the tax payer factor seen from the taxpayer's side, namely the attitudinal factor attached to taxpayers and is thought to have a strong influence on compliance with tax payments that are difficult to influence and control The source of data in this study is with taxpayers given to respondents (taxpayers) who are in the Semarang area. Descriptive research is used to describe how the effect of penalty sanctions and awareness of taxpayers that affect tax compliance. The results of this study are the effect of awareness of taxpayers and penalties of positive and significant effect on taxpayer compliance, this is indicated by the results of beta coefficients marked positive and probability values or significant levels far below 0.05.